Effect of Synbiotic on the Gut Microbiota of Cesarean Delivered Infants: A Randomized, Double-blind, Multicenter Study. Issue 1 (July 2017) - Chua, Mei Chin; Ben-Amor, Kaouther; Lay, Christophe; Neo, Anne G.E.; Chiang, Wei Chin; Rao, Rajeshwar; Chew, Charmaine; Chaithongwongwatthana, Surasith; Khemapech, Nipon; Knol, Jan; Chongsrisawat, Voranush
Abstract : ABSTRACT: We determined the effect of short-chain galacto-oligosaccharides (scGOS), long-chain fructo-oligosaccharides (lcFOS) and Bifidobacterium breve M-16V on the gut microbiota of cesarean-born infants. Infants were randomized to receive a standard formula (control), the same with scGOS/lcFOS and B. breve M-16V (synbiotic), or with scGOS/lcFOS (prebiotic) from birth until week 16, 30 subjects born vaginally were included as a reference group. Synbiotic supplementation resulted in a higher bifidobacteria proportion from day 3/5 ( P < 0.0001) until week 8 ( P = 0.041), a reduction of Enterobacteriaceae from day 3/5 ( P = 0.002) till week 12 ( P = 0.016) compared to controls. This was accompanied with a lower fecal pH and higher acetate. In the synbiotic group, B. breve M-16V was detected 6 weeks postintervention in 38.7% of the infants. This synbiotic concept supported the early modulation of Bifidobacterium in C-section born infants that was associated with the emulation of the gut physiological environment observed in vaginally delivered infants. Abstract : Supplemental Digital Content is available in the text